Theoretical Study of the Function of the IP3 Receptor / BK Channel Complex in a Single Neuron - Pérez Bonilla, María Eugenia; Reyes Monreal, Marleni; Quintero Pérez, Jessica; Pérez Escalera, Miguel; Reyes Lazalde, Arturo (Revista Mexicana de Ingenieria Biomedica, 2021)
Large conductance calcium-activated potassium (BK) channels carry out many functions in the central nervous system. The opening of BK channels requires a rise in the cytosolic calcium ([Ca2+]cyt) concentration, which can occur in two ways: calcium influx from voltage-gated calcium channels (VGCCs) located on the plasma membrane and calcium efflux through the endoplasmic reticulum (ER) membrane to the cytosol triggered by inositol 1,4,5-trisphosphate (IP3) receptors (IP3-Rs) and ryanodine receptors (RyRs). The BK channel/IP3-R/RyR interaction has been widely reported in smooth muscle but scarce information exist on neurons, where its presence is uncertain. The aim of this study was to develop a computational model of a neuron to replicate the interaction between the release of Ca2+ from the ER (through IP3-Rs and RyRs) and the opening of BK channels on the plasma membrane to regulate the level of [Ca2+]cyt, based on the Hodgkin-Huxley formalism and the Goldbeter model. The mathematical models were implemented on Visual Basic® and differential equations were solved numerically. Various conditions of BK conductance and the efflux of endoplasmic Ca2+ were explored. The results show that an abrupt increase in [Ca2+]cyt (≥ 5 mM) activates the BK channels and either pauses or stops the action potential train.